Perceptual Grouping of Closed Contours Is Disrupted by the Interpretation of the Scene Layout - Zhang, Junjun; Wan, Chaoyang; Jin, Zhenlan; Li, Ling (Frontiers in Behavioral Neuroscience, 2017)
Closure is one of the grouping principles in perceptual organization. Studies have shown that closure can be affected by several factors, specifically by low-level image features. However, the effects of high-level non-image factors on grouping by closure are unknown. In two experiments we investigated how closure is affected when depth information is introduced to the 2D closed contours, whilst the other 2D features remain intact. The first experiment showed that the grouping of closed contours was disrupted by the manipulation in 3D layout. The second experiment showed that thus disruption resulted in the impairment of searching efficiency. These findings suggest that closure is not only determined by the image features, but also affected by the interpretation of the contextual scene layout.